Assessment of the Safety Signal for the Abuse Potential of Pregabalin and Gabapentin Using the FAERS Database and Big Data Search Analytics - Papazisis, Georgios; Spachos, Dimitrios; Siafis, Spyridon; Pandria, Niki; Deligianni, Eleni; Tsakiridis, Ioannis; Goulas, Antonios (Frontiers in Psychiatry, 2021)
Introduction: The latest decade an emerging issue has been the abuse potential of the gabapentinoids pregabalin and gabapentin. The aim of our study was to further assess this safety signal combining two different methods of surveillance: The recently introduced technique based on finding patterns in search analytics big data and the disproportionality analysis of the FDA spontaneous reporting system database. Methods: Both methods were used to detect pregabalin’s and gabapentin’s abuse potential in comparison with two controls, clonazepam and levetiracetam, and further, to investigate the correlation between the search analytics and the FAERS domain. Data from the United States between 2007 and 2020Q2 were analysed. Results: Τhe FAERS analysis revealed the following pattern of signals: clonazepam > pregabalin ≥ gabapentin > levetiracetam both for the primary term ‘drug abuse and dependence’ and the secondary terms (withdrawal, tolerance, overdose). The Google domain pattern was slightly different: clonazepam ≥ gabapentin ≥ pregabalin≥ levetiracetam. A monotonic correlation was found between FAERS and Google searches for gabapentin (r=0.558; p<0.001), pregabalin (r=0.587; p<0.001) and clonazepam (r=0.295; p=0.030). Conclusion: Our results revealed that there is preliminary evidence of a safety signal for the abuse potential of pregabalin and gabapentin. Analysis of the FAERS database, supplemented by big data search analytics suggesting that there is potential of using these methods as a supplementary tool to detect drug abuse-related safety signals in pharmacovigilance.